2008
DOI: 10.1590/s1984-29612008000100008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da eficácia de extratos oleosos de frutos verdes e maduros de cinamomo (Melia azedarach) sobre Rhipicephalus (Boophilus) microplus (Acari: Ixodidae)

Abstract: RESUMOExtratos hexânicos obtidos dos frutos de Melia azedarach foram testados sobre fêmeas ingurgitadas e larvas de Rhipicephalus (Boophilus) microplus. Foram produzidos quatro extratos: um de frutos verdes e três com frutos maduros, sendo um com os frutos imediatamente processados, outro com frutos armazenados por cinco meses e um testado após armazenamento do extrato por 2 (dois) anos a 4ºC. Os testes foram feitos em triplicata, em diluições de 0,25% a 0,0156%. A eficácia dos extratos foi avaliada através da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 11 publications
0
12
1
2
Order By: Relevance
“…The efficacy was greater than what was found by Borges et al (2005), although the egg conversion and hatchability of the ticks did not differ between the two experiments. These in vivo results differed from laboratory test observations (BORGES et al, 1994, 2003, SOUSA et al, 2008, in which it had already been demonstrated that the fruit extracts of M. azedarach had higher efficacy against the females reproductive efficiency.…”
Section: In Vivo Testscontrasting
confidence: 82%
See 3 more Smart Citations
“…The efficacy was greater than what was found by Borges et al (2005), although the egg conversion and hatchability of the ticks did not differ between the two experiments. These in vivo results differed from laboratory test observations (BORGES et al, 1994, 2003, SOUSA et al, 2008, in which it had already been demonstrated that the fruit extracts of M. azedarach had higher efficacy against the females reproductive efficiency.…”
Section: In Vivo Testscontrasting
confidence: 82%
“…Storage of M. azedarach fruits for five months at room temperature caused a decrease in their acaricide effect (SOUSA et al, 2008). Yakkundi et al (1995) observed a 5% reduction in azadirachtin after one month of storage of A. indica seeds and 35% after four months.…”
Section: Difficulties Relating To the Use Of Plant Extractsmentioning
confidence: 98%
See 2 more Smart Citations
“…In Brazil, several plants have been evaluated against R. (B) microplus, highlighting Melia azadirachta (SOUSA et al, 2008), Azadirachta indica (COSTA et al, 2008), Drimys brasiliensis (RIBEIRO et al, 2008b), Piper aduncum (SILVA et al, 2009), Simarouba versicolor (CATTO et al, 2009), Calea serrata (RIBEIRO et al, 2011), Tagetes minuta (GARCIA et al, 2012) and Guarea kunthiana (BARBOSA et al, 2013).…”
Section: Introductionmentioning
confidence: 99%